Microsatellite hybrid capture technique for simultaneous isolation of various STR markers. - Prochazka, M (Genome Research, 1996)
The microsatellite hybrid capture technique was designed to enrich simultaneously for various microsatellite repeats from a genomic clone. It is illustrated in this report that different repeat motifs, including polymorphic ones, can be efficiently isolated in a single experiment. In principle, this technique can be applied to any type of genomic clones to facilitate the isolation of informative markers for fine mapping of subchromosomal regions of interest, and for linkage and association studies of candidate genes for which no polymorphic markers are available yet.
10.1101/gr.6.7.646